Optimal Relay Selection Strategy in Cognitive Cooperative Relaying Network - Yinshan Liu; Xiaofeng Zhong; Jing Wang (Dianxin kexue)
Cognitive cooperative relaying communication significantly improves the performance of wireless communication networks and spectral efficiency.Optimal relay selection problem,which characterize the desired tradeoff between the probing cost for establishing cooperative transmission and hence higher reward via cooperative diversity,is a hard issue when the number of relay nodes is large.Optimal relay selection strategy was established by using optimal stopping theory with a finite horizon.Furthermore,a pure SNR（signal-to-noise ratio）threshold structure was exhibited.Theoretical analysis and numerical results indicate that proposed optimal relay selection strategy is effective in reducing the number of probing candidate relays and improving the reward of source.